An LTR Retrotransposon-Derived Gene Displays Lineage-Specific Structural and Putative Species-Specific Functional Variations in Eutherians - Irie, Masahito; Koga, Akihiko; Kaneko-Ishino, Tomoko; Ishino, Fumitoshi (Frontiers in Chemistry, 2016)
Amongst the 11 eutherian-specific genes acquired from a sushi-ichi retrotransposon is the CCHC type zinc-finger protein-encoding gene SIRH11/ZCCHC16. Its contribution to eutherian brain evolution is implied because of its involvement in cognitive function in mice, possibly via the noradrenergic system. Although the possibility that Sirh11/Zcchc16 functions as a non-coding RNA still remains, dN/dS ratios in pairwise comparisons between its orthologs have provided supportive evidence that it acts as a protein. It became a pseudogene in armadillos (Cingulata) and sloths (Pilosa), the only two extant orders of xenarthra, which prompted us to examine the lineage-specific variations of SIRH11/ZCCHC16 in eutherians. We examined the predicted SIRH11/ZCCHC16 open reading frame (ORF) in 95 eutherian species based on the genomic DNA information in GenBank. A large variation in the SIRH11/ZCCHC16 ORF was detected in several lineages. These include a lack of a CCHC RNA-binding domain in its C-terminus, observed in gibbons (Hylobatidae: Primates) and megabats (Megachiroptera: Chiroptera). A lack of the N-terminal half, on the other hand, was observed in New World monkeys (Platyrrhini: Primates) and species belonging to New World and African Hystricognaths (Caviomorpha and Bathyergidae: Rodents) along with Cetacea and Ruminantia (Cetartiodactyla). Among the hominoids, interestingly, three out of four genera of gibbons have lost normal SIRH11/ZCCHC16 function by deletion or the lack of the CCHC RNA-binding domain. Our extensive dN/dS analysis suggests that such truncated SIRH11/ZCCHC16 ORFs are functionally diversified even within lineages. Combined, our results show that SIRH11/ZCCHC16 may contribute to the diversification of eutherians by lineage-specific structural changes after its domestication in the common eutherian ancestor, followed by putative species-specific functional changes that enhanced fitness and occurred as a consequence of complex natural selection events.